The structure of a confiscated street drug: 6-Monoacetyl morphine hydrochloride trihydrate - C19H22NO4Cl·3H2O - Wood, Matthew; Bernal, Ivan; Lalancette, Roger (European Journal of Chemistry, 2021)
Since street drugs are frequently and rapidly modified, in order to circumvent the current laws that make them illicit, it is necessary to fully identify them by single crystal X-ray diffraction; subsequently, ideal powder patterns are computed for rapid identification of additional confiscations, which are mostly available in powder form. Monoacetyl morphine is found in samples of heroin as a by-product of incomplete synthesis, or from degradation of diacetyl morphine caused by heat, humidity, or pH changes. It is formed by the hydrolysis of the acetyl function on the benzene moiety of the morphine ring, thereby inserting an OH moiety at that site. This compound, 6-monoacetyl morphine, is the primary and active metabolite of heroin, rapidly hydrolyzed in the user’s blood. Herein, we describe the structure of 6-monoacetyl morphine, IUPAC name: [(4R,4aR,7S,7aR,12bS)-9-hydroxy-3-methyl-2,4,4a,7,7a,13-hexahydro-1H-4,12-methanobenzofuro[3,2-e]isoquinolin-7-yl] acetate (A), as the trihydrated hydrochloride, whose structure has not been described previously. Our crystals belong in space group P212121 with cell parameters of a = 6.9367(2), b = 13.0374(3), c = 21.9856(6) Å, V = 1988.30 (9) Å3; its composition is C19H22NO4Cl·3H2O, and Z = 4.0. A full sphere of data was collected at 100 K using CuKα radiation (λ = 1.54178 Å), yielding 3594 unique reflections measured and a final R-factor = 4.1%, with a Flack parameter = 0.05(1).